Efeitos de um programa de treinamento físico em mulheres asmáticas. - Silva, Tatiane Lopes Patrocinio da (2006)
The aim of this study was to evaluate the effects of the lower and upper limb physical training (LLPT), arms muscle training (AMT) associated with and of the respiratory reeducation functional techniques (RFR) on asthmatic patients. The cardiopulmonary function was evaluated before and after the physical training. It was analyzed the Maximal and Submaximal cardiopulmonary test (CPT), the Heart Rate (HR), the dyspnea sensation, ventilatory and metabolic variables, the distance walked in 6 minutes, the variables of the spirometry, the respiratory muscle strength (RMS), though the maximum inspiratory pressure (PImax) and maximum expiratory pressures (PEmax), and the toracoabdominal cirtometry. Moreover it was objectified to evaluate the methods of determination of the anaerobic threshold (AT), from the ergoespirometry and lactacidemy. Nine asthmatic patients (GA) and 9 health individuals (GC) were evaluated. The asthmatic patients constituted the treated group and performed the training (PT + AMT +RFR), three times per week, during 12 weeks. The health subjects constituted the control group. The initial evaluation was consisted of an anamnesis, a physical examination, a maximal and submaximal CPT, a Spirometry and a 6WD test. Moreover, they had been submitted still to the measure of toraco-abdominal cirtometry (in the levels axillary, xifoidiano and abdominal), of the PImáx the PEmáx the Blood Pressure (HR and the Saturation of oxygen (SpO2). In the end of the training the patients were reevaluated. The individuals of the GC were submitted to the same evaluation. It was observed a significant reduction in the the values found in the RMS, spirometry, 6WD test, tolerance to exercise and peripheral muscle force (Mann-Whitney) in treated subjects when compared with health subjects. Already the treat groups had presented significant increases of the daily pay for the one after treatment in the values of PImáx and PEmáx, covered distance on 6WD. Moreover, it was observed an in increase in the HR peak, VE, VO2 peak, VCO2 peak, metabolic and ventilatory AT, speed peak, covered distance and in peripheral muscle force. It can be conclude, that the predict equation proposed to evaluate the respiratory muscle strength and covered distance on 6WD test was adequate to provided values of reference for such testes on the volunteers of this study. The 6WD test on treadmill did not differ from the 6WD on corridor and it can be an alternative on the evaluation of asthmatic individuals. The AT determinate by invasive and non-invasive methodology was similar. The association of the AMT, PT and the RFR provided an improvement in the physiological variables analyzed and can promote profits of the cardiorrespiratory performance in asthmatic patients.